PRINCIPLES OF PRESERVATION NATIONAL HISTORICAL COLORING IN TRANSLATIONS FROM UZBEK INTO ENGLISH - Ulbosin Tleumuratova Orazbaevna (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2023)
Annotation: This paper presents a comprehensive framework for preserving the national historical coloring in translations from Uzbek into English. The proposed approach incorporates annotation, keywords, input section, methods section, results section, discussion section, conclusions, and suggestions. By following these principles, translators can accurately convey the cultural and historical nuances of Uzbek texts while ensuring their faithful representation in English.